The Influence of Applying VAT on Revenues of the General Authority of Zakat and Tax “A Field Study on Makkah Region” - El-Kelety, Ibrahim Abd El-Mageed; Al-Kishan, Ismail Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify the impact of the application of VAT on the revenues of the General Authority of Zakat and Tax (GAZT) in Makkah Region. To achieve this goal, the descriptive analytical approach is applied through a questionnaire designed for this purpose that was circulated amongst a sample of examiners at the General Authority of Zakat and Tax in the Kingdom of Saudi Arabia for the region of Makkah Al-Mukarramah. The results of the study showed that there is a strong relationship between the application of VAT and the reduction of commercial cover up. The study also found that the application of VAT reduces the chances of tax evasion. In light of the results, the study recommends that the GAZT should pay attention to the field survey and activate it with the support of some government agencies because this contributes to the obligation of taxpayers to submit tax models and pay the tax. The study also recommends the need for the GAZT to disclose its Zakat and tax revenues and aspects of spending and clarify the social and economic benefits from them, which encourages taxpayers to disclose their revenues and commercial activities.
Keywords: value-added tax; tax evasion; General Authority for Zakat and Income; Saudi Arabia